Silver(I) Oxide Catalyzed C/S–H Trifluoromethylation of Arenes and Heteroarenes with Sodium Trifluoromethanesulfinate - Sadhana, Km; Kumawat, Sandeep; Jyothi, Kallakuri Leela Manikya Naga Siva; Natte, Kishore (Synlett, 2025)
We present a general and scalable approach for the C(sp2)–H or S–H trifluoromethylation of arenes and heteroarenes. This method employs bench-stable CF3SO2Na as the CF3 source, with Ag2O serving as the catalyst and K2S2O8 as the oxidant. Notably, the protocol features broad functional-group compatibility, mild conditions, and high regioselectivity. Furthermore, it is applicable to biologically relevant molecules such as caffeine, pentoxifylline, ganciclovir triacetate, and mercaptopurine.
Keywords: silver catalysis; trifluoromethylation; sodium trifluoromethanesulfinate; late-stage functionalization